Suicidal ideation and chronotype assessment in nurses and police officers - Alves,Verônica de Medeiros (2015)
BACKGROUND: Nurses and police officers are professionals that work in shifts and have jobs that require attention and responsibility. They work under conditions that can cause stress, anxiety and changes in sleep patterns. OBJECTIVE: This study aims to identify symptoms of anxiety and depression, chronotype and the presence of suicidal ideations in nurses and police officers in the city of Arapiraca/Alagoas, Brazil. METHODS: This is a descriptive and quantitative study. The interviews were conducted using (i) identification records and general data, (ii) the Beck Anxiety Inventory, (iii) the Center for Epidemiologic Studies Depression Scale and (iv) the Horne-Östberg Questionnaire. RESULTS: Fifty-three nurses and 111 police officers participated in the research. Nurses and police officers exhibited indifferent to moderate matutinal chronotypes. Most of the nurses and police officers reported minimal to light levels of anxiety. Nurses and police officers presented elevated risk for depression. Five nurses and six police officers had considered attempting suicide at the time of the research. There were no significant differences between the study groups with respect to anxiety and depression symptoms, chronotype and suicidal ideations. CONCLUSION: The nurses and police officers examined presented high risk for symptoms of anxiety and depression; a considerable number of nurses and officers had lifetime suicidal ideations. Implementation of preventive measures is necessary for the early diagnosis of anxiety and depressive disorders in order to prevent complications, including possible suicide.